Kepemimpinan Dan Budaya Organisasi Dalam Meningkatkan Dinamika Tim Dan Negosiasi Pelanggan Elsport Digital Printing - Hidayatul Mazidah; Ardista Dwi Elsania; Putri Jukhfiyah; Mitha Sintya Dwi Wahyuni; Muhammad Fais; Dimas Frendi Saputra (Shofanah Media Berkah, 2025)
This study aims to examine how leadership and organizational culture contribute to improving team dynamics and the effectiveness of customer negotiations in a digital printing and custom apparel business. The main issues in this study relate to employee character diversity, cross-divisional coordination, and the demands of maintaining service quality amidst increasing variations in customer demand. The research approach used was descriptive qualitative through in-depth interviews and direct observation of work processes. The results indicate that a delegative, communicative, and responsive leadership style can improve the effectiveness of interdivisional coordination. An organizational culture characterized by flexibility, cooperation, and open communication supports the creation of an adaptive work environment for employees with diverse characters. Furthermore, a customer negotiation strategy that prioritizes persuasive communication, clear explanations, and the use of promotional offers helps reduce the potential for complaints and increases customer satisfaction. These findings indicate that the integration of adaptive leadership, a supportive organizational culture, and relationship-based negotiation strategies is an effective solution for strengthening operational performance and service quality in a printing service business.